Uma leitura de 26 poetas hoje / A reading of 26 poetas hoje - Machado, Guacira Marcondes (Revista de Letras, 2007)
Este trabalho procura identificar selecionadas produções poéticas da antologia 26 Poetas Hoje as faces da resistência indicada por Alfredo Bosi no ensaio “Poesia Resistência”. Do “grito de alarme” pessoal de poetas pertencentes a gerações diferentes, emerge uma poesia espontânea, autêntica e, sobretudo, resistente, como produto da renovação da expressão poética, impregnado de afetividades e de intimismo e que incorporou o coloquial e os recursos da grande poesia brasileira desde 22. This reading presents a sample from this anthology and tries to identify in it the faces of resistance indicated by Alfredo Bosi in his essay: “ Poesia Resistência”. In the several manners the poets of different generations chose for their personal cry of alert we find a poetry wich is spontaneous, authentic and, above all, “resistent”. This is due mainly to the renewal of the poetical expression, impregnated with affective ness and intimism, which included colloquial language and devices used by all great Brazilian poetry since the modernism of 1922.